Changes in singing classes in the Basic Stage of Music in Turrialba, based on virtualization due to the COVID-19 pandemic in the first semester of 2020 - Castillo Calvo, Diego Armando (2026)
This study analyzes the most important changes of the singing lesson genre, from the perspective of virtualization due to the COVID-19 pandemic, at the Etapa Básica de Música Turrialba (EBMT) of Universidad de Costa Rica (UCR), Sede del Atlántico, on the first semester of 2020, specifically singing department. Therefore, a series of interviews are performed via Zoom with students of the aforementioned department, with the goal of fathom on the most important facts that affects the teaching-learning process, negative as well as positive. Based on the previous idea, the following analysis categories are included: music class, the use of “ICT's” on music lessons and the perspective of educational virtuality.